Dakwah Bil Hal Nabi Muhammad dalam Pemberdayaan Ahl al-Suffah di Madinah - Charolin Indah Roseta (STID Al-Hadid, 2026)
THE PROPHET MUHAMMAD’S DA’WAH BIL HAL IN THE EMPOWERMENT OF THE AHL AL-SUFFAH IN MEDINA. This article examines the Prophet Muhammad’s practice of dakwah bil hal in empowering the Ahl al-Suffah through the lens of Asset-Based Community Development (ABCD). Previous studies have generally portrayed the Ahl al-Suffah as an impoverished community that played a role in early Islamic education, hadith transmission, and the history of da’wah. Meanwhile, the Prophet’s empowerment process of this marginalized group has not been extensively analyzed using an asset-based empowerment perspective. To address this gap, this article employs a qualitative, literature-based method with a historical-sociological approach. Data were obtained from the Sirah Nabawiyah, hadith collections, hadith commentaries, and empowerment literature, which were analyzed using the ABCD perspective. The results of the analysis indicate that the Prophet’s empowerment took place through three stages: awareness-raising, capacity-building, and empowerment. The entire process utilized individual, social, institutional, economic, and community assets already available in Medina, enabling the Ahl al-Suffah to undergo a transformation from aid recipients into active agents serving as preachers, Quran teachers, community servants, economic actors, and drivers of Islamic community development. The main findings of this article indicate that the Prophet’s practice of empowerment aligns with the ABCD principles, while also expanding upon them through the dimensions of spiritual assets, prophetic moral leadership, and da’wah as the primary drivers of social change. These findings enrich the development of asset-based empowerment theory while providing a conceptual foundation for the practice of da’wah bil hal and the empowerment of contemporary Muslim communities.